Dynamic cooperative advertising under manufacturer and retailer level competition - Chutani, Anshuman; Sethi, Suresh P. (Elsevier, 2018)
We study dynamic cooperative advertising decisions in a market that consists of a finite number of independent manufacturers and retailers. Each manufacturer sells its product through all retailers and can offer different levels of advertising support to the retailers. Each retailer sells every manufacturer’s product and may choose to carry out a different amount of local advertising effort to promote the products. A manufacturer may offer to subsidize a fraction of the local advertising expense carried out by a retailer for its product, and this fraction is termed as that manufacturer’s subsidy rate for that retailer. We model a Stackelberg differential game with manufacturers as leaders and retailers as followers. A Nash game between the manufacturers determines their subsidy rates for the retailers and another Nash game between the retailers determines their optimal advertising efforts for the products they sell in response to manufacturers’ decisions. We obtain optimal policies in feedback form. In some special cases, we explicitly write the incentives for coop advertising as functions of different model parameters including the number of manufacturers and retailers, and study the impact of the competition at the manufacturer and the retailer levels. We analyse the profits of the players and find the model parameters under which a manufacturer benefits from a coop advertising program. Furthermore, in the case of two manufacturers and two retailers, we study the effect of various model parameters on all four subsidy rates. We also extend our model to include national level advertising by the manufacturer.